Diagnostic Pathology of Ovarian Tumors - Soslow, Robert A.; Tornos, Carmen (Springer New York : Imprint: Springer, 2011)
Diagnostic Pathology of Ovarian Tumors offers a focus on the pathology of ovarian neoplasia with detailed clinically relevant information for practicing pathologists not found in other more general volumes of gynecologic pathology. This important work focuses almost entirely on strategies for accurate diagnosis and histologic subclassification, and the clinical correlates of these diagnoses. It provides evolving guidelines for detecting early ovarian cancer in prophylactic specimens; cutting-edge information on enhancing the reproducible and clinically meaningful subclassification of ovarian carcinoma as well as new proposals for ovarian carcinoma grading. Richly illustrated, containing abundant tables and figures as well as bulleted points of information, Diagnostic Pathology of Ovarian Tumors is the first text offering chapters written by practicing gynecologists on how clinical data can enhance pathologic diagnostic accuracy, how pathologists can efficiently convey their diagnostic opinions to gynecologists, and the way in which a given diagnosis triggers a cascade of clinical testing and therapy.   Diagnostic Pathology of Ovarian Tumors will be of great value to practicing surgical pathologists, including gynecologic pathologists, pathology residents in training, as well as gynecologic and medical oncologists worldwide.